Assimilation and Contrast in Spontaneous Comparisons: Heterogeneous Effects of Standard Extremity in Facial Evaluations. Issue 1 (9th June 2020) - Barker, Paul; Dotsch, Ron; Imhoff, Roland
Judgments we make about others often depend on the standards we use as comparisons. Investigations into the outcomes of these comparisons and potential moderators have often been limited to single dimensions and preselected standards. The current work instead uses multiple evaluative facial dimensions and a multitude of comparisons. A series of 4 experiments ( N = 665) attempted to detect contrast from extreme (Study 1) and assimilation to moderate standards in within (Studies 2 and 3) and between-subjects designs (Study 4). Results showed inconsistent evidence for both comparison effects and significant heterogeneity across the evaluative dimensions that were sampled. An additional 5 studies ( N = 861) and a single-paper meta-analysis ( K = 7) revealed judgment dimension specific dynamics. Facial Extraversion produced both assimilation and contrast effects as expected; Dominance and Competence displayed only contrast; Trustworthiness showed only assimilation effects; and Likability presented no signs of either. The resulting implications for theory and measurement are discussed.